The system of assignments and exercises in forming the language personality on the profile level of studying phonetics (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The article analyzes different classifications of exercises, gives the scientific classification of assignments and exercises in forming the language personality on the profile level of studying phonetics.
Keywords: classification criteria; system of exercises; phonetic and linguistic exercises; phonetic and speech exercises; phonetic and communicative exercises and phonostylistic exercises